Gene Expression Profile Is Different between Intact and Enzymatically Digested Equine Articular Cartilage. (April 2021) - Lepage, Sarah I. M.; Sharma, Rishi; Dukoff, David; Stalker, Leanne; LaMarre, Jon; Koch, Thomas G.
Objectives: RNA isolation is necessary for the evaluation of gene expression. Due to the nature of its extracellular matrix, RNA isolation from articular hyaline cartilage is difficult and thus the tissue is commonly enzymatically digested in order to extract RNA from the obtained chondrocytes. We hypothesized that the digestion process affects the expression levels of common cartilage-associated genes. Design: Expression of cartilage-associated genes was compared between intact cartilage and digested chondrocytes from weight bearing and non-weight bearing regions of the equine fetlock joint. Results: The gene expression of SOX9, COL1A2, COL2A1, ACAN, and COLX were analyzed. Digested cartilage showed a significant decrease in the expression of COL1A2, COL2A1, and ACAN compared to intact cartilage in both joint regions, and an increase in COLX expression in non-weight bearing cartilage only. Conclusions: Enzymatic digestion of cartilage significantly impacts gene expression profile. We conclude that while RNA isolation from intact cartilage is more technically difficult, determination of gene expression should be conducted on intact cartilage if true representation of the in vivo processes is sought.